PENGARUH MEDIA PERMAINAN TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI DI SMA NEGERI 1 MARISA - Sarjon Lakoro; Sunarty Eraku; Daud Yusuf (Universitas Negeri Gorontalo, 2020)
The Effect of Crossword Puzzle Game Media on Students' Learning Outcomes in Geography Learning (A Case Study at Grade X IPS at Senior High School of SMAN 1 Marisa). This experimental study is about learning outcomes which aimed to determine significant differences in students' learning outcomes using crossword media and Powerpoint media. This employed a quantitative approach where the design forms use a posttest-only control group design. In this method, we will see how the cause and effect relationships of using treatments use crosswords and PowerPoint media. In collecting data, learning test results are used in the study sample. The sample is two classes of X IPS as an experimental class with a control class, namely class X IPS 1 consisting of 32 students as an experimental class and class X IPS 3 consisting of 31 students as a control class. To take samples, the researcher used a Clauster random sampling technique or random sampling group. Based on the results of data analysis, it was found that there was a significant difference on the learning outcomes of students who were taught using media crosswords with learning outcomes of students who were taught using powerpoint media. This is indicated by the results of the t-test. Furthermore, the value of t is t count = 4,57 and t table = 1,99. The sample is stated to be significantly different if t count greater than t table. Hypothesis test results show that t count greater than t table is 4,57 greater than 1,99. Therefore, it can be concluded that from the t-test results H0 is rejected and HI is accepted. In other words, it has a significant difference.